Cameroon : Joint Bank-Fund Debt Sustainability Analysis, 2018 Update - International Development Association; International Monetary Fund (World Bank, Washington, DC, 2018)
Cameroon’s risk of external debt distress remains high. Fiscal consolidation and the Fund-supported envisaged reforms, coupled with the increasing share of concessional new borrowing, would improve the debt profile over time. However, at present, Cameroon’s external debt remains highly vulnerable to exogenous shocks: the policy-dependent threshold for the present value of debt to exports and debt service to exports are breached in the baseline program scenario as well as under standard stress tests. Mitigating risks to public debt thus requires a number of policy actions including: (i) a resolute and effective fiscal consolidation; (ii) a shift in the composition of new borrowing towards concessional loans; (iii) enhanced controls on externally-financed investment projects at all levels of government; (iv) implementation of policies to boost growth and non-oil exports; and (iv) a strengthening of public debt management.